Utilization of Locally Available Bacteria in Degradation of Plastics - Wanjohi, L.; Mwamburi, L.; Too, E.; Kosgei, J. (Africa Environmental Review Journal, 2022)
Polythene papers have been widely used as packaging material due to their light weight, inertness and low cost. Disposable plastic cups are produced for single use and hence constitute a major source of consumer household plastic waste. The disposal of the polythene bags and disposable plastic cups is a major environmental challenge because they are not easily degraded. An inventory was taken in Lake Nakuru to determine the biodiversity of bacteria of the alkaline waters and their potential utilization in environment restoration through degradation. Samples were collected at five points of the lake selected based on their locations, proximity to fresh water inlets and depth of the lake. The samples were collected once a month for six months in the year 2011. They were kept in a cool box under ice at 4C and transported to university of Eldoret microbiology lab. Serial dilution was carried out and culturing was done using spread plate method on nutrient agar. The cultures were incubated at 35 C for 24 hours. Sub-culturing was done to obtain pure cultures which were then isolated and identified by observing their morphological characteristics, gram staining, biochemical tests, and serotyping using Analytical Profile Index Kits. The identified bacteria species were inoculated in conical flasks that contained distilled water, inorganic nutrients and disks prepared from disposable plastic cups and polythene bags to elucidate their degradation potential. Degradation potential of the bacteria was determined by calculating the percentage weight loss of the disposable plastic cups and polythene bags disks after 90 days. Twenty one different species of bacteria were identified. The following bacteria were found to be effective in degradation of disposable plastic cups and polythene bags respectively; Sphingomonas paucimobilis (17.5%, 37.5%), Streptococcus pyogenes (11.5%, 27.0%,), Tatumela ptyseas (11.0%, 21.5%), Bacillus anthracoides (6.0%,7.5%), Chryseobacterium indologenes (3%,7.5%), Chryseobacterium meningosepticum (8%,19.5%), Pseudomonas cepacia (9.5%, 35.5%), proteus penneri (4.5%, 18%), Moraxela sp.( 6.5%,19%), Alcaligene sp.(0.5%,27%), Providencia stuarti(1.5%,5.5%) and Providencia rettgeri (5.0%,13.5%). In this study, novel bacteria included Tatumella ptyseas, Proteus penneri and Providencia stuarti. These bacteria are recommended in the degradation of disposable plastic cups and polythene bags.